Analytical Investigation of the Effects of Topographic Irregularities on Peak Pressure due to Blast Waves - Mohammad Iman Khodakarami (Iranian Society of Structrual Engineering (ISSE), 2015)
Effects of propagation and scattering of high pressure waves same as blast waves are always interested for researchers. In this paper, the additional air pressure due to blast waves near topographic irregularities is considered. Regarding this study, it is clear that additional pressure from shock waves is quite different respect to the pressure in a smooth area and this pressure is involved with the weight of detonation and distance between detonation and the target point. Also in this paper, the total force s which is apply to a building in smooth location and the location near topographic irregularities is calculated and compared.